Perancangan Vidio Dokumenter Tarian Lukah Gilo - Maharian Agung; Dendra Rama Yusuf (IAM Indonesia, 2024)
The Lukah Gilo dance is a dance that requires supernatural or magical powers. This dance uses lukah (bubu) as its main property. The term Lukah Gilo comes from two words, namely Luka (bubu), which is an oval-shaped fish or eel catching tool made from woven sticks or rattan, while Gilo is the Minang word for